Preoperative evaluation of high-risk basal cell carcinoma with line-field confocal optical coherence tomography (LC-OCT) reduces Mohs micrographic surgery stage number: A case-control study - Paradisi, Andrea; Cornacchia, Luigi; Cappilli, Simone; Abeni, Damiano; Federico, Francesco; Di Stefani, Alessandro; Mannino, Maria; Peris, Ketty (EJC skin cancer, 2024)
Mohs micrographic surgery (MMS) is the preferred surgical approach for high-risk basal cell carcinoma (BCC). Pre-surgical tumor margins delineation with line field confocal optical coherence tomography (LC-OCT) is expected to reduce MMS stages number. to investigate the effectiveness of LC-OCT preoperative evaluation of high-risk BCC margins in reducing the number of MMS stages to achieve tumor clearance. high-risk BCC patients undergoing MMS at Policlinico A. Gemelli Foundation, IRCCS – Rome during January 2018 – December 2022. The LC-OCT group included patients undergoing preoperative lateral tumor margin demarcation by clinical, dermoscopic, and LC-OCT examination; patients in the control group underwent preoperative lateral tumor margin demarcation by clinical and dermoscopic examination only. LC-OCT imaging was compared to MMS histopathological sections. 63 facial high-risk BCCs from 60 patients, mean age of 68.3 years (SD 11.9). The LC-OCT and the control group included 22 and 41 BCCs, respectively. LC-OCT imaging showed almost perfect agreement with histopathology for low- versus high-risk of recurrence BCC histopathological subtypes discrimination (Cohen’s kappa 0.88). We reported a significant difference in the mean number of MMS stages between the LC-OCT and the control group (1.23 ± 0.43 SD, and 1.89 ± 1.05 SD, respectively; p-value =0.007). At univariate regression analysis, LC-OCT preoperative mapping of BCC tumor margins significantly reduced patients’ risk of undergoing >1 MMS stage (crude odds ratio [ORc]: 0.3 95% CI 0.1–0.8, p-value =0.032). LC-OCT preoperative evaluation of high-risk BCC margins significantly reduced the number of MMS stages to achieve tumor clearance. •LC-OCT preoperative evaluation of BCC margins reduces the number of Mohs stages.•LC-OCT imaging shows a strong agreement with BCC histopathological examination.•LC-OCT is useful also for aggressive BCC histopathological subtypes evaluation.